Short term heat stress alters the hematological, immunological, and plasma metabolomic responses of Florida Cracker sheep - Harrison, Makenzie; Adebayo, John Odunayo; Mills-Widemon, Anijia; Ikuejamoye-Omotore, Sola; Estrada-Reyes, Zaira M.; Ogunade, Ibukun M.; Pech-Cervantes, Andres A.; Terrill, Thomas H.; Siddique, Aftab; Ruiz-González, Alexis (Frontiers in Animal Science, 2025)
The study aimed to investigate the effects of short-term heat stress on physiological, hematological, immunological, and metabolomic responses in Florida Cracker ewes. Fourteen Florida Cracker ewes were randomly assigned to either heat stress (HT) or cooling (control, CTL) conditions, respectively, for a duration of six weeks during the summer season. Ambient temperature and relative humidity data for HT and CTL ewes were recorded weekly to estimate temperature humidity index (THI). Respiration rate and rectal temperature were measured for each experimental ewe. Blood samples were collected from each ewe at baseline (week 0) and at week 1, 2, 3, 4, 5 and 6 post-exposure for hematology analysis and plasma extraction. Plasma samples were used for analysis of IgA level and to conduct targeted metabolomics. Targeted metabolomics analyzed a total of 50 metabolites, including organic acids, amino acids, hexoses, lipids, and carnitines. The THI for the HT and CTL groups ranged from 81.3 – 89.5 and from 73.5 – 75.6, respectively. The HT group exhibited a significant increase (P < 0.05) in respiratory rate compared to the CTL group. No significant changes were observed in rectal temperature or IgA levels between the experimental groups. Hematology analysis revealed a significant increase (P < 0.05) in neutrophil count and neutrophil percentage (%) and a decrease in lymphocyte percentage (%) at week 3 in the HT group. Targeted metabolomics analysis identified 19 differentially abundant metabolites between the HT and CTL groups. Pathway enrichment analysis showed upregulation of fatty acid biosynthesis, glutathione metabolism, primary bile biosynthesis, porphyrin metabolism, and glycine, serine, and threonine metabolism (P ≤ 0.05) in the HT group compared to CTL. Our findings highlight that short-term heat stress alters the immunological, hematological, and metabolomic profile of Florida Cracker ewes. Understanding these changes can contribute to developing effective management strategies to mitigate the detrimental impact of heat stress on sheep operations in the southern U.S.